PERAN PENDIDIKAN JASMANI DAN KESEHATAN MELALUI PENDEKATAN PEMBELAJARAN INOVATIV DALAM MEMPERSIAPKAN GENERASI MILLENIAL YG SEHAT, AKTIF DAN KREATIF MENUJU INDONESIA EMAS 2045 - Ilham Kamaruddin; Nur Khozanah Ilmah (EDU RESEARCH, 2024)
Physical and Health Education (Penjasorkes) has a strategic role in shaping a healthy, active and creative millennial generation in preparation for the Golden Indonesia 2045. Innovative learning approaches, which include the use of technology, game-based learning models and holistic approaches, are key in supporting the achievement of this goal. PE focuses not only on physical development, but also on character building, social skills and creativity of learners. In the context of the millennial generation who are familiar with technology, digital integration such as the use of sports apps, gamification and social media as learning tools help to increase student interest and engagement. This research shows that innovative learning approaches can create engaging and relevant learning experiences that promote healthy lifestyles, active habits and creative thinking from an early age. Thus, innovatively designed physical education contributes to the creation of quality human resources, as the foundation for Indonesia's success in facing global challenges in 2045.